Association of peripapillary hyper‐reflective ovoid masslike structures and disease duration in primary progressive multiple sclerosis. (25th August 2021) - Wicklein, Rebecca; Wauschkuhn, Josephine; Giglhuber, Katrin; Kümpfel, Tania; Hemmer, Bernhard; Havla, Joachim; Knier, Benjamin
Abstract: Background and purpose: Peripapillary hyper‐reflective ovoid masslike structures (PHOMS) are a novel finding during retinal optical coherence tomography in patients with multiple sclerosis (MS). To date, there are no data on the occurrence of PHOMS in early MS. The aim of this study was to investigate the frequency of PHOMS in patients with first diagnosed early relapsing–remitting MS (RRMS) and to search for associations of PHOMS with disease patterns in different MS subtypes. Methods: This was a cross‐sectional analysis in two different cohorts: cohort 1, consisting of early RRMS patients ( n  = 349); cohort 2, consisting of patients with primary progressive MS (PPMS) ( n  = 66) and RRMS ( n  = 65). Results: Peripapillary hyper‐reflective ovoid masslike structures were detected in 18.3% of patients with early RRMS. The occurrence of PHOMS was not associated with age, disease duration and disability. Investigating clinical patterns and the occurrence of PHOMS (cohort 2), an association of PHOMS with higher Expanded Disability Status Scale measures (PHOMS 4.9, 3.7–6.1; no PHOMS 3.5, 3.0–5.3; p  = 0.03) and longer disease durations (PHOMS 6.5 years, 1.9–11.0; no PHOMS 1.0 years, 0.0–4.0, p  = 0.0007) was found in patients with PPMS but not RRMS. After p value adjustment, the disease duration appeared to be more relevant ( β  = 0.16, p  = 0.06). Conclusion: Peripapillary hyper‐reflective ovoid masslike structures were found in 18% of patients with early MS. The presence of PHOMS might be associated with disease progression only in PPMS but not RRMS, suggesting that PHOMS might be embedded in neurodegenerative processes. Abstract : Peripapillary hyper‐reflective ovoid masslike structures (PHOMS) were detected in 18.3% of patients with early relapsing–remitting multiple sclerosis (MS). The occurrence of PHOMS was not associated with age, disease duration and disability in these patients. From further investigations of the clinical patterns and the occurrence of PHOMS in different suptypes of MS, an association of PHOMS with longer disease durations in patients with primary progressive MS was found.